Analisis Makna Membohongi Diri pada Lirik Lagu - Suci Puji Lestari; Alex Sobur (Bandung Conference Series: Communication Management, 2023)
Abstract. The arrival of music in one's life is nothing new. Every region and culture in the world has certain music that is spoken, heard, or played at an event or historical event and in one's life journey. A songwriter can interact with his listeners with a song. Because with song lyrics, the writer can express himself about events that are happening in the world. In their creation, the songwriters use their language creativity in taking diction and integrating phenomena in society and the natural surroundings. Musicians have some meaning in arranging their lines and verses in this way, as well as their use of words, symbols, metaphors, etc. Lyrics or lyrics made by a musician must have meaning because the words used by musicians are a form of emotional expression contained in sound and words. One of Indonesia's indie musicians is Fiersa Besari, who started his career in 2021. His name skyrocketed in 2013. Then collaborated with Feby Putri and created a song called "Runtuh" with lyrics that have a deep meaning and can touch Indonesian music listeners , one meaning that is clearly visible is the meaning of deceiving oneself. The purpose of this study was to find out the meaning of self-deception in the song "Crlapse" through Roland Barthes' semiotic theory. The data collection techniques used to obtain the findings are observation, documentation, and library research. Abstrak. Datangnya musik dalam kehidupan seseorang bukan suatu hal yang baru. Setiap daerah dan budaya di dunia yang memiliki musik tertentu yang dituturkan, didengar, atau dimainkan di suatu peristiwa atau kejadian bersejarah dan dalam perjalanan hidup seseorang. Dengan lirik lagu, penulis dapat mengekspresikan dirinya terhadap kejadian yang telah terjadi. Dalam penciptaannya, para penulis lagu menggunakan kreativitas berbahasanya dalam mengambil diksi dan memadukan fenomena dalam masyarakat maupun alam sekitarnya. Lirik yang dibuat oleh seseorang musisi pasti memiliki arti karena kata-kata yang digunakan oleh musisi merupakan bentuk ekspresi emosi yang terkandung dalam suara dan kata-kata. Salah satu musisi indie Indonesia Fiersa Besari, yang mengawali karier nya pada tahun 2021, Namanya melejit pada tahun 2013. Lalu berkolaborasi bersama Feby Putri dan menciptakan sebuah lagu berjudul “Runtuh” dengan lirik yang memiliki makna yang dalam dan bisa menyentuh para pendengar musik Indonesia, salah satu makna yang terlihat jelas adalah makna membohongi diri. Makna membohongi diri ini bisa menjadi suatu hal yang buruk ataupun baik dalam sebuah realitas sosial. Tujuan “Runtuh” melalui teori semiotika Roland Barthes. Teknik pengumpulan data yang digunakan untuk mendapatkan hasil temuan yaitu observasi, dokumentasi, dan studi pustaka.